Approach to the inferior vena cava in its passage through the diaphragm an its retrohepatic path. - Salgado, Moisés; Trostchansky, José (Cirugía del Uruguay, 1976)
The authors describe the region covered by the inferior vena cava i, its passage through the diaphram. It is wrapped in its posterior face by extensions of the peritoneal and pericardic serosae and by diaphramatic ligaments prolonged by fibrous connective tissue which are attached to the fibrous pericardium or fade away and wrap its anterior face and the hepatic veins. I'herefore the openin,g in the diaphragm through which the inferior vena cava passes is neither fibrous, nor extensible nor adherent as classical literature would have. The anatomy of the region provides different approaches according to anatomical planes. There follows a description of the technique for total approach of the inferior vena cava from the pericardium to the lower edge of the liver, through the thorax, by openlng the iaphragm and ligating the lower right diaphragmatic vein.